2018
DOI: 10.1007/s12039-018-1447-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation (ODH) of Ethylbenzene with $$\hbox {CO}_{2}$$ CO 2 and $$\hbox {N}_{2}\hbox {O}$$ N 2 O over Heteropolycompounds

Abstract: Heteropolyacids of Keggin structure, H 3 PMo 12 O 40 , H 3 PMo 11 WO 40 and the salts K 3 PMo 11 WO 40 and K 2.5 Fe 0.08 H 0.26 PMo 11 WO 40 were characterized by X-ray diffraction (XRD), UV-Vis spectroscopy, Fourier transform infrared (FTIR), low-temperature nitrogen adsorption and 31 P MAS NMR spectroscopy. The acid-base properties were evaluated using the isopropanol decomposition. They were tested in oxidative dehydrogenation (ODH) of ethylbenzene in the temperature range 300-400 • C at atmospheric pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…With this important to note that the water molecules formed can promote the desorption of styrene product molecules from the catalyst surface and increase the selectivity of the process. In this regard, there is an intensive search for oxidants for the catalytic oxidation of EB in St. To the number of like oxidantrefers O 2 , SO 2 , N 2 O, CO 2 [2][3][4][5][6][7]. The latter compound, as a mild oxidizing agent, is the subject of ever-expanding research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this important to note that the water molecules formed can promote the desorption of styrene product molecules from the catalyst surface and increase the selectivity of the process. In this regard, there is an intensive search for oxidants for the catalytic oxidation of EB in St. To the number of like oxidantrefers O 2 , SO 2 , N 2 O, CO 2 [2][3][4][5][6][7]. The latter compound, as a mild oxidizing agent, is the subject of ever-expanding research.…”
Section: Introductionmentioning
confidence: 99%
“…and Kamaraju S.R.R. showed that the process on Co 3 O 4 /Al 2 O 3 proceeds in a twostep way (equations 2 and 3) [18]; In [4], the authors suggest that the process on KFePMo11W proceeds in a one-step way (1); Pak and Wislovsky [19], as well as Shuwei [12] showed that EB [20] they found that the greatest yield of styrene and selectivity for styrene in the presence of CO 2 .…”
Section: Introductionmentioning
confidence: 99%